Prediction and Validation of the Process Window for Atomic Layer Etching: HF Exposure on TiO2 - Kondati Natarajan, Suresh; Cano, Austin M; Partridge, Jonathan L; George, Steven M; Elliott, Simon D (Journal of physical chemistry. C, 2021)
A combined computational and experimental study is employed to understand the competition between self-limiting (SL) and chemical vapor etch (CVE) reactions to design an atomic layer etch (ALE) process. The pulses in an ALE process have to be self-limiting; i.e., the reactions should reach saturation after sufficient pulse time. By comparing the reaction free energies of corresponding SL and CVE reactions using density functional theory (DFT), the temperature and pressure conditions can be predicted that favor the SL or CVE reactions. The etching of TiO2 when exposed to HF gas is utilized as a test case. Simulations reveal that when TiO2 is exposed to reactant HF at a pressure of 0.2 Torr, the SL reaction removing H2O at 0.01 Torr and fluorinating the surface is preferred up to 87 °C (360 K). At higher temperatures, continuous removal of TiO2 by CVE occurs according to the reaction TiO2 + HF → TiF4 + H2O subject to kinetic activation barriers. Experimental results from in situ Fourier transform infrared (FTIR) spectroscopy and quadrupole mass spectrometry (QMS) are compared with the theoretical predictions. In good agreement with theory, the FTIR spectroscopy studies revealed an onset of spontaneous etching (CVE) at temperatures around 80–90 °C. In addition, the QMS analysis observed TiF4 and H2O as the etch products, further validating the calculations. The calculations also predicted that an increase in the reactant gas pressure would enhance etching at high temperatures. The low computational cost of this theoretical approach allows for rapid screening of etch reagents and prediction of the temperature/pressure windows where the reactions will be in the SL or CVE regimes.